Construction of Whiteness through Nomination, Predication, Argumentation and Intensification or Mitigation - Rana Bhat, Shuv Raj (Tribhuvan University Journal, 2018)
In this paper, Mary Kingsley’s Travels in West Africa has been analysed from the perspective of critical discourse analysis. In particular, how Kingsley constructs whiteness through strategies such as nomination, predication, argumentation and intensification or mitigation has been explored. The natives from minor culture are represented from the western terministic screens, to use K. Burke’s phrase. The findings show that the strategies used are related to the positive construction of self (West) and the negative presentation of Other (Africa).